2021
DOI: 10.3389/fimmu.2021.729040
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Single-Cell Analysis Reveals Regulatory Networks and Cellular Heterogeneity in Mouse Primary Sjögren’s Syndrome Salivary Glands

Abstract: Sjögren’s Syndrome (SS) is a chronic autoimmune disease of unknown etiology which primarily affects the salivary and lacrimal glands resulting in the loss of secretory function. Treatment options for SS have been hampered due to the lack of a better understanding of the underlying gene regulatory circuitry and the interplay between the myriad pathological cellular states that contribute to salivary gland dysfunction. To better elucidate the molecular nature of SS, we have performed RNA-sequencing analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 94 publications
5
18
0
Order By: Relevance
“…We also noted the downregulation of several metabolic pathways (See square on Figure 3B ). These findings correlate with the recently published data on the RNA sequencing of the NOD.H-2b mouse submandibular glands ( 25 ) and with analysis of diabetic NOD mouse model ( 33 ). Taken together our data suggests an altered lipid homeostasis during LG inflammation.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We also noted the downregulation of several metabolic pathways (See square on Figure 3B ). These findings correlate with the recently published data on the RNA sequencing of the NOD.H-2b mouse submandibular glands ( 25 ) and with analysis of diabetic NOD mouse model ( 33 ). Taken together our data suggests an altered lipid homeostasis during LG inflammation.…”
Section: Resultssupporting
confidence: 91%
“…One of the most unexpected findings was that activation of the inflammatory pathways was found in all epithelial cell clusters, suggesting that the epithelial compartments participate in the inflammatory process. The contribution of the epithelial cells to disease progression was reported for the SMG of the pSS mouse model and in patients with SS ( 25 , 82 ). Furthermore, corneal epithelial cells act as an initial physical and immunological barrier to injury/infection playing an important role in the immune response ( 83 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The subsequent DEG and KEGG analysis demonstrated that affected acinar and ductal epithelial cell subpopulations may transition to a mixed epithelial/immune cell-like state by aberrantly expressing molecules associated with immune cells. 126 In addition, combined genome-wide association studies (GWASs) and RNA-seq data for Sjogren's syndrome with human parotid gland scRNA-seq results, susceptibility genes in human parotid glands were identified. 58 Systemic lupus erythematosus (SLE), a type of chronic and even life-threatening autoimmune disease, is characterized by obscure pathogenesis and diverse manifestations.…”
Section: Analysis On Cell Hierarchy and Intercellular Heterogeneity Bymentioning
confidence: 99%
“…The scRNA‐seq was applied for detection on the diseased cell subpopulations and their expression profiles in primary Sjogren's Syndrome mouse salivary gland. The subsequent DEG and KEGG analysis demonstrated that affected acinar and ductal epithelial cell subpopulations may transition to a mixed epithelial/immune cell‐like state by aberrantly expressing molecules associated with immune cells 126 . In addition, combined genome‐wide association studies (GWASs) and RNA‐seq data for Sjogren's syndrome with human parotid gland scRNA‐seq results, susceptibility genes in human parotid glands were identified 58 …”
Section: In‐depth Study Of Oral Diseases Using Scrna‐seqmentioning
confidence: 99%